2018
DOI: 10.2147/ott.s176724
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 inhibits lung metastasis of osteosarcoma: an early investigation using an orthotopic model

Abstract: BackgroundBone morphogenetic proteins (BMPs), members of the TGF-β superfamily, are known to regulate cell proliferation, differentiation, apoptosis, chemotaxis, and angiogenesis. BMPs also participate in the development of most tissues and organs in vertebrates. Recombinant human (rh) BMPs, such as rhBMP-2, rhBMP-4, and rhBMP-7, have been recently approved to augment spinal fusion and recalcitrant long-bone non-unions because of their equivalent or superior efficacy to autogenous bone graft in enhancing bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…e concept of differentiation therapy was proposed as early as the 1970s based on the idea that the malignant cells (perhaps Cancer Stem Cells or Tumor Propagating Cells) could differentiate into less aggressive or benign cells, allowing differentiation to be an alternative or complementary strategy to chemotherapy-mediated cytotoxicity [40][41][42]. It has been shown that differentiation therapy can reduce malignancy by preventing tissue invasion and metastasis [43]. Leukemia is by far the most studied cancer for differentiation therapy and the only cancer with a successful application [44].…”
Section: Discussionmentioning
confidence: 99%
“…e concept of differentiation therapy was proposed as early as the 1970s based on the idea that the malignant cells (perhaps Cancer Stem Cells or Tumor Propagating Cells) could differentiate into less aggressive or benign cells, allowing differentiation to be an alternative or complementary strategy to chemotherapy-mediated cytotoxicity [40][41][42]. It has been shown that differentiation therapy can reduce malignancy by preventing tissue invasion and metastasis [43]. Leukemia is by far the most studied cancer for differentiation therapy and the only cancer with a successful application [44].…”
Section: Discussionmentioning
confidence: 99%
“… Gauthaman et al (2012) found that umbilical cord-derived MSCs from Wharton’s jelly suppressed the proliferation and migration of MG-63 cells (a human OS cell line) in vitro ; in a Kaposi sarcoma model, MSCs also inhibited tumor progression ( Khakoo et al, 2006 ). BMP-2 also has inhibited OS progression, although the potential mechanism was not discussed ( Xiong et al, 2018 ). Given the close link between MSCs and BMP-2 in osteoblastic differentiation and OS etiology, BMP-2 might suppress OS through BMSCs.…”
Section: Bone Morphogenic Protein-2 Inhibits Osteosarcoma Progression Via Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Moreover, BMP-2 has suppressed tumors and promoted bone formation simultaneously: Wang et al (2012) indicated that renal cell cancer was inhibited and bone formation was induced with the application of BMP-2. Furthermore, BMP-2 has reduced tumor volume, attenuated OS-induced pulmonary metastases, and stimulated bone formation ( Xiong et al, 2018 ). Applying 30 μg of BMP-2 to OS-bearing mice also increased the transcription of osteogenic genes and promoted osteogenesis ( Wang et al, 2013 ).…”
Section: Bone Morphogenic Protein-2 Inhibits Osteosarcoma Progression Via Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the clinical treatment of OS is primarily surgical, with adjunctive chemoradiotherapy and biotherapy. In recent years, immunotherapy [4,5], molecular targeted therapy [6,7], and cancer stem cell therapy [8,9] have been used increasingly for the treatment of this disease. Although the 5-year survival rate of patients with OS has increased significantly with the improvement of treatment and clinical management, therapeutic effects remain unsatisfactory in patients with metastatic and recurrent OS [10].…”
mentioning
confidence: 99%